Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content:1. Role of Human Resources Training in Building Leadership Administrative Abilities (Applied in Sahil & Sahara Bank (Headquarter), Republic of Chad)Dr. Abu Bakar Adam Daifallah, Prof. Hassabo Ahmed Hassabo2. The Role of Organizational Culture in Implementing Knowledge Management in Organizations:  An Analytical StudyMr. Arif Khamis Al-Fazari3. The application of administrative empowerment and its impact on the work environment of health institutions in the Sultanate of Oman: a case studyMs. Ghizlan Ali Mohammed Al-Bulooshi4. The impact of incentives on job satisfaction:  A field study on Al-Jamaaz Group Company in RiyadhMr. Yousef Obaid Al-Maslokhi5. The impact of social media on the consumer tendencies of store patrons in the Asir regionMr. Adnan Essa Almutairi, Prof. Hussein Mohammed Al Obaid6. Measurement and analysis of factors affecting financial Equilibrium: An analytical study in a sample of commercial banks registered on the Amman Stock Exchange (2000-2021)Teacher \ Rawaa Ahmad Yousef7. The Impact of Video Game Dimensions on Brand Love: A Guide for the Gaming Industry 2023-2024Mr. Soliman Hamdy Hassan Youssef, Ms. Alaa Tarek Khalil Abdellatif
Keywords: Journal of Economic, Administrative and Legal Sciences